Traumatic Counseling for Children Affected by The Tsunami Disaster - Hunainah, Hunainah; Riswanto, Dody (Universitas Negeri Semarang, 2021)
The background of this research is the Sundanese Straits tsunami disaster in 2018 which caused casualties, death, serious injuries, minor injuries, loss of shelter, transportation, and materials. Survivors of the tsunami tragedy impacted psychological disorders in the form of post-disaster trauma. The purpose of this scientific research is to look at the psychological impact of post-disaster trauma experienced by children and the handling methods used through traumatic counseling. This is because children have weak mental or psychological conditions compared to adults in the face of trauma. The method used is a qualitative approach. Data collection techniques are interviews, documentation studies, and audio-visual information. The research location is in the area of ​​Labuan Pandeglang, Banten. Respondents numbered 50 children, research conducted on December 24 2018 - January 30 2019 by two counselors from two universities in Banten. Data analysis is done by reviewing all primary data and forming interpretation data or propositions in the form of meaning. The findings of the research are survivors conducting traumatic counseling in children consisting of 4 stages, namely (1) physical health examination; (2) counseling using the traumatic healing method; (3) play therapy; (4) psychological assistance in the form of cognitive behavioral therapy (CBT) therapy. This research can provide recommendations to researchers in the future, especially those relating to the psychological handling of victims of natural disasters. This research is recommended to all survivors, volunteers, and counselors who are concerned with handling post-disaster trauma victims, not only for the tsunami disaster.